The Influence of Work Experience, Supervision and Work Discipline on Employee Performance on CV. Star NineConvection business is a very popular type of business in Indonesia. The popularity of convection business is mainly due to two things. First, becaus - Danny Mahendra Widya Putra; Abid Muhtarom; Mohammad Yaskun (Sean Institute, 2025)
Convection business is a very popular type of business in Indonesia. The popularity of convection business is mainly due to two things. First, because the products produced by the convection industry, namely clothing, are one of the basic human needs, the market for the convection business will always exist. Convection market share. Secondly, the convection business has become popular because the entry barrier to starting this business is not too big. This research method uses a type of quantitative research with data taken from CV employees. Star Nine Lamongan with a total of 60 people. This study uses multiple linear regression test, determination coefficient test, ujit and f test.This study found that there is a significant influence between work experience, supervision, and work discipline on employee performance both simultaneously and partially, with work experience as the most dominant variable.